Evaluasi Metode Pendugaan Laju Evapotranspirasi Standar (ETo) Menggunakan Bahasa Pemograman Visual Basic Microsoft Excel di Kabupaten Nagan Raya Aceh: Evaluation of Standard Evapotranspiration Rate Estimation Method (ETo) Using Microsoft Excel Visual Basic Programming Language in Nagan Raya Aceh District - Adlan; Setiawan, Budi Indra; Arif, Chusnul; Saptomo, Satyanto Krido (Jurnal Teknik Sipil dan Lingkungan, 2021)
Estimation of evaporation rate is needed in hydrological data, especially in irrigation and drainage planning data. The method for estimating the evapotranspiration rate recommended by FAO is the Penman - Monteith method, however apart from this method there are still several methods that can be used if the data obtained in the field are different. Evaluation of the method of estimating the rate of evapotranspration is expected to help in choosing the right method when different data is obtained, so with this evaluation, we can see the accuracy of the methods. The methods that are closest to accuracy with the Penman - Monteith method are Hargreaves, Makkink, Turc, Blaney-Cridlle and Penman. If ordered based on the ranking of the evaluation results, the method that is closest to the Penman - Monteith method is Hargreaves, because of all the evaluation variabels Hargreaves has the best evaluation value. While the closest model based on the best R2 value is the Jensen-Haise model, but the error value of this model is very high.